From urban space to cyberspace: A research on spatial writing and human-android relations in do androids dream of electric sheep? - Mi, Chen; Omar, Noritah; Zainal, Zainor Izat; Awang, Mohammad Ewan (Academy Publication, 2023)
Philip K. Dick takes the highly computerized but ruined Los Angeles of the United States after the post-apocalyptic war as the background and brings the cyberspace struggle between androids and humans as the novel's theme, sketching a cyberpunk society in which humans and androids fight against each other. The novel Do Androids Dream of Electric Sheep? invites people to think about cyberspace and human-androids subjectivity. Inspired by Slavoj Zizek's critical theory of cyberspace, this paper uses this science-fiction force as a text to explore how contemporary American science fiction reconstructs a revolutionary human-androids subject in cyberspace, challenging human subjectivity in the urban space. Faced with human-android coexistence, Dick affirms the coexistence of multiple subjects using equal dialogue, fully exploits the advantages of androids and humans, and constructs the subject with human-androids. Through an in-depth study of androids, this paper concludes that in a human-androids coexistence space, humans and androids should not be in a master-slave relationship; instead, they are each other's constitutive Other. Humans should try to break the boundary between self and others to accept a pluralistic and open subject.